2017
DOI: 10.18517/ijaseit.7.5.2526
|View full text |Cite
|
Sign up to set email alerts
|

Grasp Stability Analysis of an Isotropic Direct Driven Three-Finger Soft Robot Hand

Abstract: Grasp stability is considered to be an important aspect in object manipulation of a multifingered robot hand. Multifingered hand contacts the object at some arbitrary locations during the object manipulation and applies the gripping force to hold and manipulate the object without slip. It is desirable to use the optimum gripping force during the grasp manipulation for two reasons; firstly, to prevent the object from damages, secondly, to decrease the cost of the manipulation. With these objectives in mind, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Examples of research on force control, particularly for the robotic hand can be found in [10][11][12]. Most of these research studies aim mainly to create a biomechanically realistic human hand.…”
Section: The Materials Methods 21 Literature Review (Finger Rehabilitamentioning
confidence: 99%
“…Examples of research on force control, particularly for the robotic hand can be found in [10][11][12]. Most of these research studies aim mainly to create a biomechanically realistic human hand.…”
Section: The Materials Methods 21 Literature Review (Finger Rehabilitamentioning
confidence: 99%
“…The conventional two-finger type gripper has a single grasping posture, which makes it difficult to achieve stable and efficient picking in complex environments. The three-fingered gripper has the characteristics of strong grasping force, flexible contact, and strong adaptability [7,8]. In complex environments, it can accomplish the grasping of objects in different postures.…”
Section: Introductionmentioning
confidence: 99%